Temporary Botulinum Immobilization of Residuum Muscles for Facilitation of the Initial Ingrowth of Skin to the Porous Skin and Bone Integrated Pylon in the Technology of Direct Skeletal Attachment: Large Animal Model - Bohart, Zachary; Cassidy, Charles; Merrill, David; Villani, Mario; Villani, Rosanna; Cappabianca, Leo; Pitkin, Mark (Frontiers in Rehabilitation Sciences, 2022)
Enhancing the technology of bone-anchored limb prosthetics, we present a modified porcine model for developing an infection-free integration between skin and a percutaneous bone implant. The deeply porous Skin and Bone Integrated Pylon (SBIP) presented an infection-free skin-implant interface both after implantation into dorsum and after implantation into the residuum after below-knee amputation. However, deep ingrowth of skin into the porous cladding of the SBIP was achieved better in the dorsal procedure, while implantation to the residuum sometimes developed a stoma, probably due to the high mobility of the skin and soft tissues in the pig’s thigh. Uncontrolled high skin mobility during the first weeks after implantation constituted a limitation for the porcine animal model, which we tried to address in the current study. As our previous studies showed that casting of the leg residuum did not sufficiently limit the skin’s movement around the implant, we tested a modified protocol of the implantation, which included injection of Botox into the thigh muscles. During the course of the study we identified proper Botox componentry, dosage and period after injections to achieve a maximal effect of immobilization of the muscles affecting skin movements. To verify the immobilization, we used kinetic data on asymmetry of loading during gait with the Strideway system, Tekscan, Inc., Boston, MA. We found that injections in the four muscles of the distal thigh of the left hind leg with MYOBLOC® (rimabotulinumtoxinB; 5,000 Units/muscle) were sufficient to provide noticeable immobilization by the fourth week after the procedure. This conclusion was made based on the analysis of the dynamics of asymmetry in vertical ground reactions on the injected (left hind) and uninvolved (right hind) legs during gait over an instrumented walkway.